THE TRANSFORMATION OF THE VICTIMOLOGY PARADIGM IN THE INDONESIAN CRIMINAL JUSTICE SYSTEM: STRENGTHENING VICTIM PROTECTION THROUGH RESTORATIVE JUSTICE AND HUMAN RIGHTS-BASED JUSTICE APPROACHES - Siregar, Syawal Amry (Jurnal Ilmiah METADATA, 2025)
This article examines the paradigm transformation in victimology within Indonesia's criminal justice system, analyzing the evolution from retributive to restorative approaches in protecting crime victims. The research investigates how international human rights frameworks have influenced Indonesian legal reforms, particularly through the implementation of Law No. 31 of 2014 on Witness and Victim Protection and the 2023 Criminal Code. Employing a normative-empirical legal research methodology with qualitative analysis, this study examines statutory regulations, judicial decisions, and implementation practices across multiple jurisdictions in Indonesia. The findings reveal a significant paradigm shift toward victim-centered justice, evidenced by enhanced restitution mechanisms, victim impact statement integration, and community-based restorative justice programs. However, substantial implementation gaps persist, including limited awareness among law enforcement officials, inadequate funding for victim support services, and cultural barriers to restorative approaches in certain communities. The research identifies critical challenges: inconsistent application of restorative justice principles across jurisdictions, insufficient training for criminal justice practitioners, and the tension between traditional retributive justice expectations and emerging restorative paradigms. Comparative analysis with victimology developments in progressive jurisdictions demonstrates that Indonesia's legal framework has made considerable progress, yet practical implementation requires systematic capacity building, increased inter-agency coordination, and sustained commitment to human rights principles. This article contributes to the scholarly discourse on victimology by providing comprehensive analysis of Indonesia's transition toward victim protection, offering policy recommendations for strengthening restorative justice mechanisms, and proposing an integrated framework that harmonizes traditional justice values with contemporary human rights standards. The study concludes that successful paradigm transformation requires not merely legislative reform but comprehensive systemic change encompassing institutional capacity, cultural sensitivity, and unwavering commitment to victim dignity and rights restoration.